2021
DOI: 10.3390/v13050890
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Persistent Viral Shedding in the Context of Hydroxychloroquine-Azithromycin Treatment

Abstract: SARS-CoV-2 nasopharyngeal shedding contributes to the spread of the COVID-19 epidemic. Among 3271 COVID-19 patients treated at the Hospital University Institute Méditerranée Infection, Marseille, France from 3 March to 27 April 2020, tested at least twice by qRT-PCR, the median SARS-CoV-2 nasopharyngeal shedding duration was 6 days (range 2–54 days). Compared with short shedders (qRT-PCR positivity < 10 days), 34 (1.04%) persistent shedders (qRT-PCR positivity ≥ 17 days; mean ± SD: 23.3 ± 3.8 days) were sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…In their recent article published in Viruses, Michel Drancourt and colleagues [ 1 ] have made an interesting but underestimated side-observation. As shown in Figure 1 , they were able to isolate infectious SARS-CoV-2 virus from a clinical sample with a low concentration of viral RNA, which is reflected by a PCR Ct-value of 33.…”
mentioning
confidence: 99%
“…In their recent article published in Viruses, Michel Drancourt and colleagues [ 1 ] have made an interesting but underestimated side-observation. As shown in Figure 1 , they were able to isolate infectious SARS-CoV-2 virus from a clinical sample with a low concentration of viral RNA, which is reflected by a PCR Ct-value of 33.…”
mentioning
confidence: 99%
“…17 However, there are also data about successful isolation of infectious virus in samples up to 1-2 months during follow-up. [18][19][20] In one study, the authors demonstrated a better correlation between an Ag-RDT and culture positivity than between rRT-PCR and culture positivity; therefore, an Ag-RDT might be better suited to determining potential infectivity. 21 The main advantage of using an Ag-RDT compared to rRT-PCR is that an Ag-RDT provides a fast result and detects most of the samples with higher viral load.…”
Section: Discussionmentioning
confidence: 99%
“…The elderly might be at greater risk for prolonged viral shedding due to their weakened immune system. However, viral persistence was significantly associated with older age in some studies [ 15 , 16 ] but not in others [ 17 , 18 , 19 ]. Extended viral carriage is theoretically prone to the emergence of viral mutants in the case of antiviral therapies, as is observed for HIV infection.…”
Section: Introductionmentioning
confidence: 98%